Structural characterization of a human Fc fragment engineered for lack of effector functions - Oganesyan, Vaheh (International Union of Crystallography, 2008)
The first three-dimensional structure of a human Fc fragment genetically engineered for the elimination of its ability to mediate antibody-dependent cell-mediated cytotoxicity and complement-dependent cytotoxicity is reported. When introduced into the lower hinge and C(H)2 domain of human IgG1 molecules, the triple mutation L234F/L235E/P331S (‘TM’) causes a profound decrease in their binding to human CD64, CD32A, CD16 and C1q. Enzymatically produced Fc/TM fragment was crystallized and its structure was solved at a resolution of 2.3 Å using molecular replacement. This study revealed that the three-dimensional structure of Fc/TM is very similar to those of other human Fc fragments in the experimentally visible region spanning residues 236–445. Thus, the dramatic broad-ranging effects of TM on IgG binding to several effector molecules cannot be explained in terms of major structural rearrangements in this portion of the Fc.